PREDICTIVE GREY MARKOV CHAIN MODEL FOR PITTING CORROSION IN PIPLINES - YU ShuRong; HAN JunYu; LI ShuXin (Jixie qiangdu)
Based on the Grey theory and Markov Chain theory,two prediction models were built,they are Grey Markov Chain prediction model based on absolute distribution（ GMCAD） and Grey Markov Chain prediction model based on probability summation（ GMCPS）. These two models were used to predict the corrosion life of the oil-gas pipeline. Firstly,the calculation method of pit depth was built by the Grey theory. Secondly,test of Markov property was done to verify its feasibility. At last,GMCAD and GMCPS were used,respectively,to predict the corrosion state of the pipeline and results were compared. It indicates that both two models can give a correct prediction and the result from GMCPS is more accurate.